5-(x+3)+3x+3(x+2)=

Simple and best practice solution for 5-(x+3)+3x+3(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(x+3)+3x+3(x+2)= equation:


Simplifying
5 + -1(x + 3) + 3x + 3(x + 2) = 0

Reorder the terms:
5 + -1(3 + x) + 3x + 3(x + 2) = 0
5 + (3 * -1 + x * -1) + 3x + 3(x + 2) = 0
5 + (-3 + -1x) + 3x + 3(x + 2) = 0

Reorder the terms:
5 + -3 + -1x + 3x + 3(2 + x) = 0
5 + -3 + -1x + 3x + (2 * 3 + x * 3) = 0
5 + -3 + -1x + 3x + (6 + 3x) = 0

Reorder the terms:
5 + -3 + 6 + -1x + 3x + 3x = 0

Combine like terms: 5 + -3 = 2
2 + 6 + -1x + 3x + 3x = 0

Combine like terms: 2 + 6 = 8
8 + -1x + 3x + 3x = 0

Combine like terms: -1x + 3x = 2x
8 + 2x + 3x = 0

Combine like terms: 2x + 3x = 5x
8 + 5x = 0

Solving
8 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 5x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 5x = 0 + -8
5x = 0 + -8

Combine like terms: 0 + -8 = -8
5x = -8

Divide each side by '5'.
x = -1.6

Simplifying
x = -1.6

See similar equations:

| -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 | | 8y-6=4y-18 | | 3a+22=7a+14 | | 2n-8=6n-32 | | 2(2x+6)=5x+9 | | 16x+27=75 | | -18=6k+6(1+3k) | | 2n-8=6n-(-32) | | f-14=6f | | 4(x+3)-12=3(x-6) | | 4x^3-12x^2-64x+192=0 | | -12=5v+2+2v | | -3b+2b-3b=6 | | 7h-18=31 | | 3x-11=-14 | | -6Y+4(Y-7)=-18 | | -20-8n=-4(n+8) | | 10x+6(300-x)=2000 | | 7d^2+18b+8=0 |

Equations solver categories